1984
DOI: 10.1080/00926238408405951
|View full text |Cite
|
Sign up to set email alerts
|

Extramarital sexual crisis: Common themes and therapy implications

Abstract: The extramarital crisis situation is defined and six common themes presented. These distinguishing features: cognitive and emotional turmoil, unresolved relationship issues, defensiveness, pressures related to the extramarital partner(s), search for an interpretive framework, and decisions about the future, are elaborated in terms of existing literature in the field of extramarital sex. The six themes constitute a general profile from which therapists can formulate specific client assessments. Therapy implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…Apparently, in a significant number of couples, men and women perceive quite differently the meaning of extramarital sex with regard to the marital relationship. On the basis of the answers of the respondents in our study, we fully agree with Thompson's (1984) assumption that extramarital sex among women is often motivated by "pull" factors of curiosity about a new experience, and sometimes the search for personal growth, whereas among men the "push" factors of an unsatisfactory marriage are more frequently reported as the precursors of EMR.…”
Section: Extramarital Involvementsupporting
confidence: 81%
See 1 more Smart Citation
“…Apparently, in a significant number of couples, men and women perceive quite differently the meaning of extramarital sex with regard to the marital relationship. On the basis of the answers of the respondents in our study, we fully agree with Thompson's (1984) assumption that extramarital sex among women is often motivated by "pull" factors of curiosity about a new experience, and sometimes the search for personal growth, whereas among men the "push" factors of an unsatisfactory marriage are more frequently reported as the precursors of EMR.…”
Section: Extramarital Involvementsupporting
confidence: 81%
“…Many recent studies show that between 40–50% of all married males and females among Western, urban middle‐class couples engage in extramarital relations (EMR) within the first 10 years of their marriage (Thompson, 1984). A survey that we conducted in five randomly chosen kibbutz communities in 1984 showed similar figures: 39% of 412 kibbutz couples (married on the average for 9 years), in response to a questionnaire sent by us assuring anonimity and professional secrecy, reported that they had been involved in EMR.…”
Section: Determinants Of Breakupmentioning
confidence: 99%
“…Unfortunately, resources for recovery after an affair are not well developed for suffering individuals or the professionals trying to help them. The literature indicates that 50 to 75% of men and 35 to 50% of women have an affair before they reach 40 years of age (Marett, 1990;Thompson, 1984). Given the dearth in both professional and nonprofessional literature, After the Affair is a particularly welcome addition to the resource pool.…”
mentioning
confidence: 95%
“…They have observed that couples experience intense emotions that often vacillate between rage towards the participating partner and more inward feelings of shame, depression, powerlessness, victimization, and abandonment (see, e.g., Brown, 1991;Cano & O'Leary, 2000;Pittman, 1989;Spring, 1996;Thompson, 1984;Westfall, 1989). This emotional turmoil is often accompanied by a corresponding cognitive upheaval.…”
mentioning
confidence: 97%